Corporate Effective Tax Rates for Research and Policy - Petr Jansky (Charles University in Prague, Institute of Economic Studies (IES), 2020)
How much companies pay in corporate income taxes is often better captured by effective tax rates (ETRs) rather than by statutory ones. Economists further distinguish between those modelled using the law - forward-looking ETRs - and those estimated from actual data on companies' profits and taxes - backward-looking ETRs. Moving beyond this binary distinction, I present a spectrum where backward-looking ETRs are further broken down by the type of data used to estimate them and where all ETRs may be located along with applicable statutory rates. Within that spectrum, I focus on backward-looking ETRs and, specifically, on those estimated using companies' balance sheet databases. Based on my review of recent findings, I argue that backward-looking ETRs - of multinational corporations in particular - have become more frequently estimated thanks to advances in data availability while also becoming more relevant as a result of ongoing global corporate tax reform debates. Ultimately, I argue that the full range of various ETRs can play a useful role in both research and policy.
Keywords: C81; F21; F23; H25; H26; 330; corporate income tax; effective tax rate; forward-looking effective tax rate; backward-looking effective tax rate; multinational corporation; profit shifting